What's Your Brand of Poison? - Abd Razak, Dzulkifli (1995)
TOBACCO IN ANY FORM IS undoubtedly a poisonous substance (see Healthtrack, May 30, June 6,13,20 and 27). Alcohol is another dangerous poison man is exposed to. However, for many centuries, man has develop a societal norm whereby alcohol is socially and legally acceptable. But alcohol is just as open to abuse as any other drugs of abuse. As such many countries see fit to have some form of legislation to control the consumption and sale of alcohol. Such legislation seek to control aspects such as where alcohol can be sold, the number that can be sold, location of outlets and shops selling alcohol, age limits on the buyers of alcohol and so on. The need for such stringent restrictions are indicative of the fact that alcohol is a dangerous substance, no matter how some people perceive it.